Remains of ruined shrines in the Jain temple complex - Temples of India Project Team (Jio Institute, 2024)
To the west of the main temple, there are remains of many other shrines which might have been part of a larger Jain complex. Most part of the superstructure of these shrines are dilapidated. These dismantled portions can be seen in the vicinity of the temple. The only noteworthy remains are damaged by colossal images of Jina. The temple plan consists of a mandapa (pillared hall) and a garbhagriha (sanctum sanctorum) in plan.